Harnessing the Energy Potential and Value-Added Products from the Treatment of Sugarcane Vinasse: Maximizing Methane Production Through Co-Digestion with Sugarcane Molasses and Enhanced Organic Loading - Ribeiro, Alexandre Rodrigues; Devens, Kauanna Uyara; Camargo, Franciele Pereira [UNESP]; Sakamoto, Isabel Kimiko; Varesche, Maria Bernadete Amâncio; Silva, Edson Luiz (Springer Nature, 2025)
This study assessed the impact of organic loading rate (OLR) on methane (CH4) production in the anaerobic co-digestion (AcoD) of sugarcane vinasse and molasses (SVM) (1:1 ratio) within a thermophilic fluidized bed reactor (AFBR). The OLR ranged from 5 to 27.5 kg COD.m−3.d−1, with a fixed hydraulic retention time (HRT) of 24 h. Organic matter removal varied from 56 to 84%, peaking at an OLR of 5 kg COD.m−3.d−1. Maximum CH4 yield (MY) (272.6 mL CH4.g−1CODrem) occurred at an OLR of 7.5 kg COD.m−3.d−1, while the highest CH4 production rate (MPR) (4.0 L CH4.L−1.d−1) and energy potential (E.P.) (250.5 kJ.d−1) were observed at an OLR of 20 kg COD.m−3.d−1. The AFBR exhibited stability across all OLR. At 22.5 kg COD.m−3.d−1, a decrease in MY indicated methanogenesis imbalance and inhibitory organic compound accumulation. OLR influenced microbial populations, with Firmicutes and Thermotogota constituting 43.9% at 7.5 kg COD.m−3.d−1, and Firmicutes dominating (52.7%) at 27.5 kg COD.m−3.d−1. Methanosarcina (38.9%) and hydrogenotrophic Methanothermobacter (37.6%) were the prevalent archaea at 7.5 kg COD.m−3.d−1 and 27.5 kg COD.m−3.d−1, respectively. Therefore, this study demonstrates that the organic loading rate significantly influences the efficiency of methane production and the stability of microbial communities during the anaerobic co-digestion of sugarcane vinasse and molasses, indicating that optimized conditions can maximize energy yield and maintain methanogenic balance.
Keywords: Anaerobic biorefinery; Metabolic inference; Methanosarcina; Molasse; Vinasse